Prevalence and geographical variation of dementia in New Zealand from 2012 to 2015: Brief report utilising routinely collected data within the Integrated Data Infrastructure. (11th May 2020) - Walesby, Katherine Elizabeth; Exeter, Daniel John; Gibb, Sheree; Wood, Philip Clive; Starr, John Michael; Russ, Tom Charles
Abstract: Objectives: There are no national dementia epidemiological studies using New Zealand (NZ) data. NZ routinely collects health‐care data within the Integrated Data Infrastructure (IDI). The study objectives were to 1) investigate late‐onset dementia estimates using the IDI between 2012‐2015 and compare these with 2) published estimates, and 3) variations between North and South Islands and ethnicity. Methods: A population‐based, retrospective cohort design was applied to routinely collected de‐identified health/administrative IDI data. Dementia was defined by ICD‐10‐AM dementia codes or anti‐dementia drugs. Results: Approximately 2% of those aged ≥60 years had dementia, lower than published estimates. Dementia was higher in North Island; in 80‐ to 89‐year‐olds; among the Māori population when age‐standardised, and 9% of all dementia cases had >1 dementia sub‐type. Conclusions: To our knowledge, this is the first study ascertaining dementia estimates using NZ's whole‐of‐population IDI data. Estimates were lower than existing NZ estimates, for several reasons. Further work is required, including expanding IDI data sets, to develop future estimates that better reflect NZ's diverse population.